Pengembangan Media Booklet dalam Membantu Pengaturan Diet Penderita DM Tipe 2 - Vadira Rahma Sari; Agustina Endah Werdiharini (Politeknik Negeri Jember, 2020)
Setting a diet for people with Diabetes Mellitus is an important element in the management of diabetes. The success level of dietary arrangement depends on the behavior of patients in following the recommended dietary rules. These rules include the food count, type of food and schedule of meals. Knowledge is the main thing that must be possessed in implementing dietary arrangement. Providing information that is usually done is through counseling. Supporting media can also be provided as a support to increase knowledge and make it easier for patients to do a diet. Booklet can be an alternative. The purpose of this study was to determine the properness of booklet based on the assessment of material expert and media expert. This research is research and development or R & D (Research and Development) using the ADDIE model which consists of five steps, namely analyze, design, development, implementation and evaluation. In this R & D the researcher developed a health education media in the form of booklet. Furthermore, the booklet was tested by material expert and media expert. The effectiveness of booklet will be tested by giving pretest and posttest and product assessment questionnaire on 10 people with type 2 Diabetes Mellitus. The conclusion of this study is that booklet are made suitable to help diet arrangement for people with type 2 Diabetes Mellitus and the level of knowledge of type 2 Diabetes Mellitus patients increases after giving pretest and posttest.